Effects of a partitioned aquaculture system on water quality and growth of Penaeus vannamei. (2nd May 2019) - Li, Junwei; Guo, Yongjian; Zhu, Changbo; Ma, Zhenhua; Qin, Jian G.; Xie, Xiaoyong; Chen, Suwen
Abstract: The effects of system partition on the water quality were studied using three shrimp ponds (Ts), and each one of the shrimp pond was connected individually with a fish pond by piping and pump. Three other isolated shrimp ponds were designated as the Cs treatment. The results showed that the implementation of the system can improve the water quality in the shrimp ponds. Particulate organic matter (POM), chemical oxygen demand (COD), nitrite nitrogen (NO2 –N) and nitrate nitrogen (NO3 –N) in the Ts were lower than those in the Cs during the experiment, and in some cases, they were significantly lower ( p < 0.05). Throughout most of the experimental period, the soluble reactive phosphorus in the Ts treatment were greater than that in the Cs treatment ( p < 0.05), and N/P ratio of the water column was lower in the Ts treatment than in the Cs treatment throughout most of the experimental period ( p < 0.05). These results indicate that the partitioned system contributed to the stability of water quality and N/P ratio in the water. Vibrio parahaemolyticus was dominant in the third to seventh weeks in Cs, and the dominant condition was found only in seventh week in Ts. The result indicated that system may contribute to the slowing down of the breakout of V. parahaemolyticus in the shrimp pond. According to the redundancy analysis, COD, chlorophyll a and POM were mainly positively related to the dominance index of V. parahaemolyticus, and maybe POM can serve as an indicator to reflect the trend of V. parahaemolyticus .